A Mitigating Over-Indebtedness in Woman-Led MSMEs: A Behavioral Perspective on Financial Literacy and Self-Framing Control under Financial Stress - Putri Purwaningtyas; Bambang Agus Pramuka; Intan Shaferi; Wiwiek Rabiatul Adawiyah; Dian Purnomo Jati (Universitas Pendidikan Ganesha, 2025)
This research investigates the financial literacy and self-framing control of over-indebtedness in women-led Micro, Small, and Medium Enterprises (MSMEs). Addressing a gap where these behavioral bias remain under-explored in over-indebtedness in the context woman MSMEs. This article identifying factors that influence debt cycles in woman-led MSME, which are uniquely characterized by a dual-motive conflict between the drive for business expansion and the immediate needs of household survival. Employing a mixed-methods approach, the study analyzed a quantitative dataset of 280 women entrepreneurs in Banyumas Regency, Indonesia using SEM-PLS, complemented by qualitative insights from Focus Group Discussions and in-depth interviews. The results confirm that Financial Literacy and Self-Framing Control have a significant negative relationship with over-indebtedness. Interestingly, the moderation hypotheses were rejected. Financial stress did not significantly weaken the financial literacy or self-framing control. This suggests that women entrepreneurs exhibit functional resilience, in which their decision-making capabilities have habituated to stressful environments and remain stable under such conditions. The study challenges the ego-depletion hypothesis, suggesting that rationality and self-control are limited and decline under pressure. The findings provide a practical framework for MSME resilience by evaluating the need for behavior-oriented financial coaching that prioritizes the physical separation of business and domestic funds through communal support systems. Additionally, the study addresses the regulatory gap in multiple borrowing, proposing that policy interventions must prioritize integrated credit monitoring across all financial institutions.